USE OF NEW INNOVATIVE METHODS IN TEACHING (Proceedings of International Educators Conference, 2023)
Today, all spheres of the life of New Uzbekistan have become a field of deep reforms. In this process, it is impossible not to emphasize the changes in the educational system, which is the basis of the social sphere. The beginning of the implemented reforms, first of all, in the field of education and training, implies the incomparable role and importance of the education system, which is considered the most important link in human education in the process of globalization, in the life of our society. The attention paid by our state to the education system, in particular: the adoption of comprehensive measures related to the development of this sector in the following years, the wide range of opportunities created for young people, indicate that the reforms aimed at the education system are at the state level.